ChemInform Abstract: Recent Advances in Porous Graphene Materials for Supercapacitor Applications. Issue 2 (January 2015) - Zhang, Xiong; Zhang, Haitao; Li, Chen; Wang, Kai; Sun, Xianzhong; Ma, Yanwei
Abstract Review: 224 refs.